-5p+-4(-p+4)=

Simple and best practice solution for -5p+-4(-p+4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5p+-4(-p+4)= equation:


Simplifying
-5p + -4(-1p + 4) = 0

Reorder the terms:
-5p + -4(4 + -1p) = 0
-5p + (4 * -4 + -1p * -4) = 0
-5p + (-16 + 4p) = 0

Reorder the terms:
-16 + -5p + 4p = 0

Combine like terms: -5p + 4p = -1p
-16 + -1p = 0

Solving
-16 + -1p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '16' to each side of the equation.
-16 + 16 + -1p = 0 + 16

Combine like terms: -16 + 16 = 0
0 + -1p = 0 + 16
-1p = 0 + 16

Combine like terms: 0 + 16 = 16
-1p = 16

Divide each side by '-1'.
p = -16

Simplifying
p = -16

See similar equations:

| 8-11=-13 | | -7x-3=-38 | | y*86=259 | | -5y+3z=12 | | -4(8+7h)+2= | | 9x+9=3y+6 | | 9+9x=6+3y | | 3ab-ab= | | 2x-=3 | | 3y+6=9x+9 | | -9(-9+3j)= | | 6x+y+8x+2y=180 | | -2(a+1)-3(1-7a)=-24 | | 6x+y+8x+2y=0 | | 2x+4x+6x-2(x+3)=34 | | 6(2j+1)+7= | | 8+4x=5x+4 | | -1+5(x+2)=12x+3-17x | | X+3x+2x+3(x+1)=30 | | 5-16=8.5 | | 3x-6y+9= | | 3(4+10x)+x= | | 8x+4x=5x+4 | | x^4-4x^3-x^2+16x=0 | | 2x-3(-5x+8)=17x-2+8 | | 5(a+4)-6a+1=12 | | -8(y+2)-16=16 | | -1+5(x+2)=12x+3-1x | | 3y^4-13y^2-10=0 | | 28+2x-1=3x+22 | | 19.5(13.3-4.4x)=7.2(0.8x-116) | | 4(5t+10)= |

Equations solver categories